Differences Between Discovery Learning And Case-Based Learning Using Animated Videos On Critical Thinking Skills In Start Triage Among Undergraduate Nursing Students - Sari, Rystika Angga; Larasati, Retno; Sari Hayati, Yati (Syntax Corporation Indonesia, 2024)
The 2004 disaster in Aceh underscores the need to strengthen disaster triage preparedness. Triage would be more accurate when considering human resource factors. Students are educated nurse candidates who will serve the community through their ability to think critically. Innovative learning opens opportunities to sharpen critical thinking in students' preparedness for emergency disaster situations. This study analyzes the differences between discovery learning and case-based learning on critical thinking in START Triage among undergraduate nursing students. This quasi-experimental study used a pre-test and post-test design involving 40 undergraduate nursing students selected through purposive sampling and divided into two groups: control and intervention. Data collection utilized the Critical Thinking Disposition Inventory questionnaire. The results of the Paired T-test revealed differences in critical thinking ability in START Triage before and after receiving discovery learning and case-based learning. Furthermore, the independent T-test results indicated a significant influence of case-based and discovery learning on critical thinking ability in START Triage. Case-based learning utilizing animated videos significantly impacted nursing students' critical thinking ability in START Triage. Using animated videos as a basis for case-based learning provides a foundation for educational institutions to integrate into learning activities and disaster simulation exercises to enhance the quality of Triage services.